2021
DOI: 10.3991/ijet.v16i02.17015
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment or Limitation of the Teachers’ Rights and Abilities in the Prevailing Digital Environment

Abstract: Digital education is actually a product of recent years, although it existed before in various forms. Obviously, modern devices and means of transmitting infor-mation are necessary for its development. Modern “virtual lectures”, e-learning courses, online testing, educational resources portals, as well as digital school registers and educational process monitoring systems have become everyday real-ity. However, the digitalization of the educational system has both positive and negative side. The purpose of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…However, the effectiveness of this development can only be assessed by evaluating the teachers' perception of the use of DCC tools and the teaching results obtained in the classroom on concrete actions [7][8][9]. In this area, it has been found that the positive perception of the use of DCC tools in the classroom by teachers does not always coincide with the real capacity of teachers to adapt their programs to the virtual classroom with digital resources [10,11]. This deficit in the development of digital competence seems to be greater when we refer to the creation of digital content [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…However, the effectiveness of this development can only be assessed by evaluating the teachers' perception of the use of DCC tools and the teaching results obtained in the classroom on concrete actions [7][8][9]. In this area, it has been found that the positive perception of the use of DCC tools in the classroom by teachers does not always coincide with the real capacity of teachers to adapt their programs to the virtual classroom with digital resources [10,11]. This deficit in the development of digital competence seems to be greater when we refer to the creation of digital content [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Multicultural education fosters understanding and support for new phenomena of cultural diversity, which can facilitate the educational impact of such experiential learning (Yun & Zhang, 2017). When creating curricula for pedagogical students, it is necessary to justify ways to integrate diversity within programs, provide learning opportunities to help future educators apply innovative strategies, and link multicultural theory to practice in their own learning (Alismail, 2016;Toktamysov et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary approaches to teaching and learning history include historical thinking and historical research that emphasize the role of the student in the construction of historical knowledge. A competency-based approach to learning has recently become popular (Toktamysov et al, 2021). Historical research refers to the practice of asking questions, collecting and evaluating relevant evidence, and drawing conclusions based on that historical evidence.…”
Section: Methodsmentioning
confidence: 99%